Bloodstream infections by gram‐negative bacteria in kidney transplant patients: Incidence, risk factors, and outcome. Issue 6 (26th August 2020) - Tsikala‐Vafea, Maria; Basoulis, Dimitrios; Pavlopoulou, Ioanna; Darema, Maria; Deliolanis, John; Daikos, George L.; Boletis, John; Psichogiou, Mina
Abstract: Background: Kidney transplant recipients (KTRs) are at increased risk of infections. Methods: The aims of this study were to describe the incidence of bloodstream infections (BSIs) by gram‐negative bacteria in a cohort of KTRs, the risk factors for BSI due to multi‐drug–resistant (MDR) gram‐negative bacteria, and the predictors for unfavorable outcome, defined as death or nephrectomy or return to dialysis, within 30 days from BSI. We conducted a retrospective cohort study at the renal transplant unit of a tertiary care hospital in Athens, Greece. Results: In a total of 1962 KTRs, we recorded 195 BSI episodes in 182 single patients (male/female = 97/85), with a median (interquartile range) age of 57.2 (44‐64.9) years. The incidence was 1.393/100 patient‐years. The most common source of infection was urinary tract (70.9%), and Escherichia coli (63.7%) was the most common pathogen. 19.2% of the infecting organisms were MDR; previous antibiotic use (OR 8.2; CI 2.1‐32.9) and previous stay in the intensive care unit (OR 34.2; CI 1.6‐730.2) were associated with MDR BSIs. 6% of patients died, and 2.2% underwent nephrectomy, while no patients had to return to dialysis. Diabetes mellitus (OR 8.1; 95% CI 1.3‐50.3), Pseudomonas aeruginosa BSI (OR 46.1; 95% CI 3.9‐552.3), and septic shock (OR 46.7; 95% CI 1.7‐1304.9) were independent predictors of unfavorable outcome. Conclusion: Bloodstream infections in KTRs have a significant impact on allograft and patients outcome.